The effect of nurses' attitudes towards evidence-based nursing on the level of compliance with isolation measures in nurses caring for liver transplant patients - Gurkan, Kapikiran; Okutan, Serafettin; Aktura, Seher Cevik; Cici, Remziye (Wiley, 2025)
ObjectiveLiver transplant recipients are at a high risk of infection during the first month. Therefore, it is crucial to implement isolation measures correctly to prevent the spread of nosocomial infections. Evidence-based practices and proper implementation of isolation measures can significantly reduce morbidity and mortality. The study aimed to investigate the impact of nurses' attitudes towards evidence-based nursing on their compliance with isolation measures.MethodsThis is a descriptive study conducted between October 2023 and January 2024, with the participation of 137 nurses working in the organ transplant clinics of a university hospital in Turkey. Data was collected using a participant introduction form, the attitudes towards evidence-based nursing scale, and the compliance with isolation measures scale.ResultsThe mean total score for the scale of attitudes towards evidence-based nursing among nurses was 55.95 +/- 10.43 (15-75). Similarly, the mean total score for the scale of compliance with isolation measures was 71.44 +/- 13.53 (18-90). Both scores were above the middle level. The study found a moderately significant positive correlation between attitudes towards evidence-based nursing and compliance with isolation measures (r: 0.670, p: 0.000). The regression model showed that the attitude towards evidence-based nursing explained 44.9% of the positivity towards isolation measures (R2 = 0.449).ConclusionsThe study found a positive correlation between nurses' positive attitudes towards evidence-based nursing and their compliance with isolation precautions when caring for liver transplant patients. This highlights the significance of evidence-based nursing in patient care and the importance of adhering to isolation measures to prevent nosocomial infections.
Keywords: evidence-based medicine; liver transplantation; patient care